Effect of aperture field distribution on the maximum radiated power at atmospheric pressure - 赵朋程;郭立新 (Chinese physics B, 2017)
The air breakdown in the high-power antenna near-field region limits the enhancement of the radiated power. A model coupling the field equivalent principle and the electron number density equation is presented to study the breakdown process in the near-field region of the circular aperture antenna at atmospheric pressure. Simulation results show that, although the electric field in the near-field region is nonuniform, the electron diffusion has small influence on the breakdown process when the initial electron number density is uniform in space. The field magnitude distribution on the aperture plays an important role in the maximum radiated power above which the air breakdown occurs. The maximum radiated power also depends on the phase difference of the fields at the center and edge of the aperture, especially for the uniform field magnitude distribution.